2019
DOI: 10.1039/c9fo00284g
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid ameliorates AKT-driven hepatic steatosis in mice by suppressing de novo lipogenesis via the AKT/SREBP-1/FASN pathway

Abstract: Ellagic acid alleviates hepatic lipid accumulation in mice by suppressing AKT-driven de novo lipogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…Upon binding to EGFR, EGF activates PI3K/Akt, PLC-γ1 and MEK/ERK1/2 pathways [37][38][39]. Previous studies have shown that inhibition of the Akt/mTOR pathway in GMECs decreases the expressions of genes related to fatty acid synthesis, such as FASN, ACC and SCD1 genes [40,41]. In our study, suppression of Akt activity by its specific inhibitor MK2206 resulted in the downregulation of mRNA levels of FASN and SCD1 genes in GMECs.…”
Section: Plc-γ1 and Pi3k/akt Signaling Is Involved In The Lipid Metabsupporting
confidence: 61%
“…Upon binding to EGFR, EGF activates PI3K/Akt, PLC-γ1 and MEK/ERK1/2 pathways [37][38][39]. Previous studies have shown that inhibition of the Akt/mTOR pathway in GMECs decreases the expressions of genes related to fatty acid synthesis, such as FASN, ACC and SCD1 genes [40,41]. In our study, suppression of Akt activity by its specific inhibitor MK2206 resulted in the downregulation of mRNA levels of FASN and SCD1 genes in GMECs.…”
Section: Plc-γ1 and Pi3k/akt Signaling Is Involved In The Lipid Metabsupporting
confidence: 61%
“…Our data show that Vermentino leaf extract triggered activation of AKT1 via phosphorylation as well as increased FASN mRNA levels in MCF-7 and SKBR-3 cells. Activated AKT1 stimulates FASN expression by gene modulation of sterol regulatory element-binding protein 1c (SREBP1C), which is a transcription factor that activates FASN by binding to its promoter region [45]. Here, we provide evidence that increased AKT1 activation and the related increase in FASN mRNA compensate for Vermentino-induced FASN downregulation.…”
Section: Discussionmentioning
confidence: 84%
“…Our data shows that Vermentino leaf extract triggered activation of AKT1 via phosphorylation as well as increased FASN mRNA levels in MCF-7 and SKBR-3 cells. Activated AKT1 stimulates FASN expression by gene modulation of sterol regulatory element-binding protein 1c (SREBP1C), which is a transcription factor that activates FASN by binding to its promoter region (29). Here, we provide evidence that increased AKT1 activation and the related increase in FASN mRNA compensate for Vermentino-induced FASN downregulation.…”
Section: Discussionmentioning
confidence: 84%